Three‐dimensional interventional photoacoustic imaging for biopsy needle guidance with a linear array transducer. Issue 12 (2nd September 2019) - Wang, Hang; Liu, Songde; Wang, Tong; Zhang, Chenxi; Feng, Ting; Tian, Chao
Abstract: Needle placement is important for many clinical interventions, such as tissue biopsy, regional anesthesia and drug delivery. It is essential to visualize the spatial position of the needle and the target tissue during the interventions using appropriate imaging techniques. Based on the contrast of optical absorption, photoacoustic imaging is well suited for the guidance of interventional procedures. However, conventional photoacoustic imaging typically provides two‐dimensional (2D) slices of the region of interest and could only visualize the needle and the target when they are within the imaging plane of the probe at the same time. This requires great alignment skill and effort. To ease this problem, we developed a 3D interventional photoacoustic imaging technique by fast scanning a linear array ultrasound probe and stitching acquired image slices. in vivo sentinel lymph node biopsy experiment shows that the technique could precisely locate a needle and a sentinel lymph node in a tissue volume while a perfusion experiment demonstrates that the technique could visualize the 3D distribution of injected methylene blue dye underneath the skin at high temporal and spatial resolution. The proposed technique provides a practical way for photoacoustic image‐guided interventions. Abstract : Photoacoustic imaging has become an important imaging tool for interventional procedures. However, two‐dimensional (2D) photoacoustic image can only provide cross‐sectional information of the device and biological tissues and has limited applications in practice. A 3D image technique using a linear array ultrasound probe is proposed for biopsy needle guidance. in vivo results show the technique could simultaneously track the biopsy needle and visualize biological tissues at high speed and high resolution.